Chestnut Honey and Bacteriophage Application to Control Pseudomonas aeruginosa and Escherichia coli Biofilms: Evaluation in an ex vivo Wound Model - Oliveira, Ana; Sousa, Jéssica C.; Silva, Ana C.; Melo, Luís D. R.; Sillankorva, Sanna (Frontiers in Microbiology, 2018)
Chronic skin wounds represent a major burn both economically and socially. Pseudomonas aeruginosa and Escherichia coli are among the most common colonizers of infected wounds and are prolific biofilm formers. Biofilms are a major problem in infections due to their increasingly difficult control and eradication, and tolerance to multiple prescribed drugs. As so, alternative methods are necessary. Bacteriophages (phages) and honey are both seen as a promising approach for biofilm related infections. Phages have specificity towards a bacterial genus, species or even strain, self-replicating nature, and avoid dysbiosis. Honey has gained acknowledgment due to its antibacterial, antioxidant and anti-inflammatory and wound healing properties. In this work, the effect E. coli and P. aeruginosa phages vB_EcoS_CEB_EC3a and vB_PaeP_PAO1-D and chestnut honey alone, and combined were tested using in vitro (polystyrene) and ex vivo (porcine skin) models and against mono and dual-species biofilms of these bacteria. In general, colonization was higher in the porcine skins and the presence of a second microorganism in a consortium of species did not affect the effectiveness of the treatments. The antibacterial effect of combined therapy against dual-species biofilms led to bacterial reductions that were greater for biofilms formed on polystyrene than on skin. Monospecies biofilms of E. coli were better destroyed with phages and honey than P. aeruginosa monospecies biofilms. Overall, the combined phage-honey formulations resulted in higher efficacies possibly due to honeys capacity to damage the bacterial cell membrane and also to its ability to penetrate the biofilm matrix, promoting and enhancing the subsequent phage infection.